Hydrolysis rates of extracellular chitinase produced by piezo-philic and piezo-sensitive marine bacteria under high hydrostatic pressure - Maria Papadimitraki; Urban Wünsch; Ronnie N Glud (PANGAEA, 2025)
A high-pressure cuvette system (up to 110 MPa) with three sapphire windows was developed for real-time absorption and fluorescence measurements, along with temperature control. As a case study, extracellular chitinase activity from two spiezo-sensitive strains of Vibrio anguillarum (PF430-3 and Ba35, isolated in Chile and USA, respectively) and piezophilic Photobacterium profundum (DB110, isolated in Sulu Sea, Philippines) was assessed between 0.1–100 MPa at 10?°C. Chitinase stability was monitored over 24 h at 0.1 and 100 MPa, with fluorescence recorded every 32 minutes. Background and substrate (4-MUF-NAG) fluorescence stability under pressure were confirmed. V. anguillarum strains were cultured at 0.1 MPa whereas P. profundum was cultured at 0.1 and 28 MPa. For the acquisition of the chitinase rates, pressure was increased in 20 MPa increments until a maximum of 100 MPa and at each pressure level, measurements were recorded for one hour at a frequency of 5-10 minutes. Enzymatic recovery rates at 0.1 MPa were also measured post-pressurization.